2010
DOI: 10.1007/s10457-010-9308-9
|View full text |Cite
|
Sign up to set email alerts
|

Do multipurpose companion trees affect high value timber trees in a silvopastoral plantation system?

Abstract: Establishment of native timber trees on deforested land may contribute to the livelihood of farmers, to improved ecosystem services and to increased greenhouse gas uptake. Here, we present a new silvopastoral planting design to assess species performance and interspecific competition or facilitation effects among native timber and multipurpose trees in Central America. Two timber species, Tabebuia rosea and Cedrela odorata, were established in three low-density planting regimes allowing combined tree and futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 56 publications
(72 reference statements)
1
33
2
4
Order By: Relevance
“…A wide range of survival rates for C. odorata can be found in other studies, which are, however, all below the high rates observed here [6,47,50,51] with the exception of the study by von Breugel et al [48] which looked at a variety of sites and also found survival rates of up to 90%. Due to high mortality rates, Plath et al [47] suggested C. odorata might best be planted at sites with well-drained soils. is was not supported by our study, as the high clay content of the present soils, which tended to be waterlogged during the rainy season, did not seem to adversely affect tree survival.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…A wide range of survival rates for C. odorata can be found in other studies, which are, however, all below the high rates observed here [6,47,50,51] with the exception of the study by von Breugel et al [48] which looked at a variety of sites and also found survival rates of up to 90%. Due to high mortality rates, Plath et al [47] suggested C. odorata might best be planted at sites with well-drained soils. is was not supported by our study, as the high clay content of the present soils, which tended to be waterlogged during the rainy season, did not seem to adversely affect tree survival.…”
Section: Discussioncontrasting
confidence: 52%
“…Maize should be considered with caution, due to the comparably high mortality of trees observed in this treatment. In another study in Panama, leguminous companion trees in silvopastoral systems did not have an effect on the growth performance of C. odorata within the �rst two years [47]. One possible explanation might be that the shrub species used in this study-C. cajan-is relatively fast growing, reaching up to 3 m aer 4 months, compared to the used leguminous trees in the cited study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…DC., a member of the Bignoniaceae family, is a tree growing in tropical forests (Woodson et al 1973) from the sea level to 1,200 m (Gentry 1992). This species is used for urban ornamentation (Joselin et al 2013), for furniture and general construction (Petrone & Preti 2010, Joselin et al 2013, in agroforestry (Cajas-Giron & Sinclair 2001, Petrone & Preti 2010, Plath et al 2011) and as a medicinal plant (Ugbabe et al 2010, Jiménez-González et al 2013. Even some studies suggest this species might be employed to develop anticancer medicines (Sathiya & Muthuchelian 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Even some studies suggest this species might be employed to develop anticancer medicines (Sathiya & Muthuchelian 2010). T. rosea is also important for its potential use in reforestation and ecological restoration programs (Hernández Gil et al 2010, Castro-Marin et al 2011, Plath et al 2011). This utility is because its management is well-known…”
Section: Introductionmentioning
confidence: 99%